2018
DOI: 10.1186/s12913-018-2939-7
|View full text |Cite
|
Sign up to set email alerts
|

Beyond coverage: improving the quality of antenatal care delivery through integrated mentorship and quality improvement at health centers in rural Rwanda

Abstract: BackgroundInadequate antenatal care (ANC) can lead to missed diagnosis of danger signs or delayed referral to emergency obstetrical care, contributing to maternal mortality. In developing countries, ANC quality is often limited by skill and knowledge gaps of the health workforce. In 2011, the Mentorship, Enhanced Supervision for Healthcare and Quality Improvement (MESH-QI) program was implemented to strengthen providers’ ANC performance at 21 rural health centers in Rwanda. We evaluated the effect of MESH-QI o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 37 publications
1
45
0
1
Order By: Relevance
“…However, since many forms of HDP (GH, CH, and PE without severe features), may be clinically unapparent at onset, a significant number of pregnant women with subclinical HDP could also have been missed by studies included in this report, in a context where utilization of ANC and institutional delivery services is relatively low . Yet, among pregnant women who attend ANC in Africa, the timing of visits, considered as a practical way of preventing adverse pregnancy outcomes, is not always adequate; even when adequate, the quality of ANC care is often suboptimal, as blood pressure and proteinuria measurement may not be routinely available . Second, the uneven distribution of risk factors for HDP between high‐income countries and Africa, where women are more frequently of low socioeconomic background, are more likely to have a maternal infection or anemia, could partly explain the higher rate of HDP in the region.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, since many forms of HDP (GH, CH, and PE without severe features), may be clinically unapparent at onset, a significant number of pregnant women with subclinical HDP could also have been missed by studies included in this report, in a context where utilization of ANC and institutional delivery services is relatively low . Yet, among pregnant women who attend ANC in Africa, the timing of visits, considered as a practical way of preventing adverse pregnancy outcomes, is not always adequate; even when adequate, the quality of ANC care is often suboptimal, as blood pressure and proteinuria measurement may not be routinely available . Second, the uneven distribution of risk factors for HDP between high‐income countries and Africa, where women are more frequently of low socioeconomic background, are more likely to have a maternal infection or anemia, could partly explain the higher rate of HDP in the region.…”
Section: Discussionmentioning
confidence: 98%
“…30,31 Yet, among pregnant women who attend ANC in Africa, the timing of visits, considered as a practical way of preventing F I G U R E 1 Meta-analysis of the prevalence of overall hypertensive disorders of pregnancy adverse pregnancy outcomes, is not always adequate 33 ; even when adequate, the quality of ANC care is often suboptimal, as blood pressure and proteinuria measurement may not be routinely available. 34 Second, the uneven distribution of risk factors for HDP between high-income countries and Africa, where women are more frequently of low socioeconomic background, are more likely to have a maternal infection or anemia, 16 could partly explain the higher rate of HDP in the region.…”
Section: Subgroup Analysis Of Hdp Prevalence In Africamentioning
confidence: 99%
“…15 These strategies are effective at improving quality of care in low-and middle-income countries across a variety of clinical areas, 16,17 including Integrated Management of Childhood Illness, 18,19 drug management and prescription practices, 20,21 primary care, 22 malaria case management, 23 voluntary male circumcision, 24 and reproductive health. 25,26 Although some studies have reported associations between increased intensity of coachingrelated activities and improved quality of care, [21][22][23] the optimal coaching intensity needed to promote and sustain behavior change is unknown. Coaching intensity can be quantified across multiple domains, including frequency (e.g., 2 coaching visits per week); duration (e.g., 6 weeks of coaching); and cumulative dose, which reflects both the frequency and the duration of the intervention (e.g., 2 sessions per week for 6 weeks equals 12 cumulative visits).…”
Section: Introductionmentioning
confidence: 99%
“…A primary symptom of this poor quality is low adherence to medical protocols [1,2,3,4,5,6,7,8,9,10,11]. Given the significant evidence that increases in protocol adherence are one of the most effective ways to improve outcomes and prevent childhood deaths [12,13,14,15], a continued focus on process quality seems appropriate.…”
Section: Introductionmentioning
confidence: 99%